A Site‐Specific Charge Carrier Control in Monolithic Integrated Amorphous Oxide Semiconductors and Circuits with Locally Induced Optical‐Doping Process. (1st August 2019) - Kim, Kyung‐Tae; Jeon, Seong‐Pil; Lee, Woobin; Jo, Jeong‐Wan; Heo, Jae Sang; Kim, Insoo; Kim, Yong‐Hoon; Park, Sung Kyu
Abstract: Amorphous oxide semiconductor (AOS) thin film transistors (TFTs) have found cutting‐edge applications in sensor technologies. To reduce manufacturing costs, sensors, analog front end, and digital signal processing circuits need to be integrated on the identical substrate. Unlike traditional silicon‐based devices, optimizations for locally controllable electrical parameters of the AOSs have rarely been investigated. Here, photoactivated combustion reduction is utilized as doping motivation for solution‐processed amorphous indium–gallium–zinc oxide ( a ‐IGZO) to tune their electrical performance. By controlling parameters of a ‐IGZO TFTs, which can be partly doped with covering the desired area of the identical substrate, it is possible to match the particular threshold voltage for various circuits. For circuit optimization, automatic integrated circuit modeling spice is carried out to find the best match of the complementary metal–oxide semiconductor circuits. Finally, the site‐specific performance of switching TFTs, amplifiers, and ring oscillators implemented with low‐temperature solution‐processed a ‐IGZO and p‐type single‐walled carbon nanotube TFTs is demonstrated. The optical‐doped a ‐IGZO TFTs exhibiting a saturation mobility of >9.15 cm 2 V −1 s −1 with a locally tunable threshold voltage of −5 – 1.5 V are realized, enabling monolithic integration of functional devices. The resultant circuits demonstrate excellent amplification of 24 dB and an oscillation frequency of 12 kHz for 7‐stage ring oscillators. Abstract : A facile site‐specific optical‐doping process is realized to locally control the charge carrier concentration of low‐temperature solution‐processed a ‐IGZO thin films. It can be used as a general route to fabricate practical on‐chip applications implemented with diverse optimized amorphous oxide semiconductor devices such as switching thin film transistors, analogue amplifiers, and digital ring oscillators.